PENETAPAN BERAS SEBAGAI ALAT UNTUK MEMBAYAR ZAKAT FITRAH MELALUI METODE IYAS MENURUT MADZHAB SYAFE’I - Rahmat, Saepul; Sayehu, Sayehu; Mukarromah, Oom (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Qiyas is one way to resolve various legal cases whose arguments are not clearly stated in the ur'anqand Hadith. Imam Syafi'i is one of the initiators of the concept of iyas who holds the view that various legal cases that exist in Muslim society which are not yet clearly regulated in the ur'an and hadith can be resolved through iyas, either in the form of iyas aulawi, iyas musawi or qiyas adn . One case that is not yet clear is the type of staple food that is issued as zakat fitrah in Indonesia. The zakat fitrah issued which was the staple food of the Prophet Muhammad saw and the Arabs in ancient times was wheat, dates, cheese, and others. In fact, the majority of Muslims in Indonesia who adhere to the Shafi'i school of thought pay zakat fitrah in the form of staple foods that are commonly consumed, namely rice, corn, sago, etc. Zakat fitrah which must be paid by every Muslim who is still alive in the month of Ramadan and has excess staple food for the night and Eid al-Fitr, if rice is used is 2.5 kg or 3.5 liters per person